ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KETIMPANGAN DISTRIBUSI PENDAPATAN DI PULAU JAWA - Ingra Sovita, Yenni Del Rosa (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2016)
Inequality of income distribution is affected by the economic and non economic factorssuch as the Gross Domestic Product (GDP), population (POP), Unemployment Rate (TPT)and Degree of Fiscal Decentralization (DDF). This study aims to determine the effect ofthe GDP, population, unemployment rate and the degree of fiscal decentralization to theunequal distribution of income partially and simultaneously at the 5% significance level.The research data used in the form of data crossection in 6 provinces in Java with a datatime series in 2009 - 2015. The data was processed with panel data analysis with fixedeffect regression models. Based on the classic assumption test turns out normaldistribution of data for Jarque Bera value greater than 5%, does not occur because theprobability value results heteroskedastisitas regression residuals squared 0.9768 (greaterthan 5%), do not occur multikolinearitas, no autocorrelation for test DW 1 , 46375 and dcount is greater than dU and 4 <- dU. The regression equation fixed effect model IG it =-8.723781 + 0.278708 Ln PDRBK it + 0.65660 Ln POP it + 0.013688 Ln TPK it +0.000775 Ln DDF it + eit. Partially significant positive effect on income distribution is theGDP, population and the unemployment rate is open each probability value is less than5% (0,000 < 5%; 0,014 < 5%, 0.0261 < 5%) Simultaneously all independent variablessignificant positive effect on inequality of income distribution because F probability valueis less than 5% (0.0000 < 5%). The independent variables are able to explain thedependent variable only amounted to 78.59% while the remaining 21.41% influenced byother factors not included in the research model.Keywords: unequal distribution of income, domestic gross, population,unemployment rate open and the degree of fiscal decentralization.